Hubungan Pengetahuan Wartawan Dengan Pemberitaan LGBT di Koran Sindo - Dudi Iskandar; Muhamad Isnaini (Communication, 2018)
ABSTRACTThis study focuses on the relationship of religious knowledge and news about LGBT (Lesbian, Gay, Bisexual, and Transgender) in Koran Sindo newspaper. This research based on LGBT as reality which increasingly rampant in everyday. This research used survey method to editor of Koran Sindo by spreading questioner. Editors are the ones who process and authorize to bring down a story, including about LGBT. Based on the research that has been done, it can be drawn conclusion. Firstly, the religious knowledge of the respondents was not influenced by previous religious education, religious routines and understanding of the meaning of reading the Qur'an. Secondly, respondents have a high knowledge of religious knowledge aspect. This is evident from the average score of 26 item of questions that is able to pass the standard weight of 75. Thirdly, respondents also have a higher attitude to objective on the news about LGBT, by high score completeness news, namely 82.5 and writing placement, amounting to 69,6. Fourthly, there is a positive correlation of religious knowledge of the respondents with the news on LGBT. This is proven by hypothesis which statistically reject Ho and accept Ha.Keywords : Journalistic, LGBT, Religion, NewsABSTRAKPenelitian ini fokus pada hubungan pengetahuan agama dan pemberitaan tentang LGBT (Lesbian, Gay, Bisexual, and Transgender) di Koran Sindo. Penelitian ini berangkat dari realitas LGBT yang kian marak di kehidupan keseharian dan kemudian diangkat menjadi berita oleh media massa, termasuk Koran Sindo. Penelitian ini menggunakan metode survei terhadap redaktur Koran Sindo dengan cara menyebar kuesioner. Redaktur adalah yang mengolah dan berwenang menurunkan sebuah berita, termasuk tentang LGBT. Berdasarkan penelitian yang telah dilakukan, maka dapat ditarik simpulan sebagai berikut. Pertama, pengetahun agama para responden ternyata tidak dipengaruhi oleh pendidikan agama sebelumnya (pesantren/madrasah) rutinitas mengikuti pengajian/taklim, dan pemahaman atas makna bacaan Alquran. Kedua, responden mempunyai pengetahuan yang tinggi menyangkut aspek pengetahuan agama. Hal ini terbukti dari rata-rata skor 26 item pertanyaan yang mampu melewati bobot standar 75. Ketiga, responden juga punya sikap yang lebih tinggi untuk objektif atas pemberitaan tentang LGBT, yang dibuktinya dari tingginya skor kelengkapan berita, yakni 82,5 dan penempatan tulisan, sebesar 69,6. Keempat, terdapat hubungan/korelasi yang positif pengetahuan agama para responden dengan pemberitaan mengenai LGBT. Hal ini terbukti dengan uji hipotesis yang secara statistik menolak Ho dan menerima Ha.Kata Kunci : Jurnalistik, LGBT, Agama, Berita